Resistensi dalam Wacana Dhagelan Youtube Cak Silo Cs - Indriani, Puspita; Darni, Darni; Pairin, Udjang; Yohanes, Budinuryanta (LP. Ma'arif Janggan Magetan, 2023)
This research aims to reveal resistance strategies to form humor in Cak Silo Cs' Dhagelan YouTube content. The research data source is the YouTube content of Cak Silo Cs episode Cak Silo Jualan Pentol which was uploaded on March 22 2020. The object of research is lingual units which indicate resistance. Next, listening and interpreting were carried out and explained descriptively qualitatively and analyzed using the functional pragmatic method. The research results show that the resistance used only includes three forms of the four existing forms. 1) reactance by mocking with reasons that are not commonly used, and saying clearly